The effectiveness of distance learning in teaching in light of the Corona pandemic from the point of view of teachers of Marka District schools in Jordan - Azzam, Taghreed Mustafa (Journal of Educational and Psychological Sciences, 2022)
The study aimed to reveal the effectiveness of using distance learning in transferring educational content to students appropriately by teachers, and in a way that approaches school learning, in addition to identifying the pros and cons of using distance learning by teachers, The researcher followed the descriptive survey method for its suitability for the purposes of this study. The study population consisted of male and female teachers in the Marka District Education Directorate. The study sample consisted of (142) male and female teachers in the schools of the Marka District Education Directorate, to whom a questionnaire was applied to the effectiveness of distance learning tools prepared by the researcher, whose validity and reliability were verified .The results showed that the overall arithmetic mean of the learning effectiveness axis was (62.08), which is a weak percentage (41.72%). As for the arithmetic average and the percentage of the axis of your lesson platform, it reached (82.30), which is also a weak degree, and the percentage (46.16%), while the most important obstacles that teachers dealt with was the poor readiness and readiness of educational environments and infrastructure in schools to learn through your lesson platform. The study also found that there are no statistically significant differences for the effectiveness of distance learning at the significance level (α≥0.05) from the teachers’ point of view attributed to educational experience and academic qualification, while there were statistically significant differences for the effectiveness of distance learning at the significance level (α≤0.05) from the teachers’ point of view attributed to the interaction between academic qualifications and teaching experience. The study came out with a set of recommendations, the most important of which are: Developing your lesson platform to become interactive between the teacher and the student.